POLA ASUH ORANG TUA TERHADAP KEGIATAN BELAJAR ANAK DI RUMAH (Studi Pada Anak Tunarungu SLB Panam Mulia Kelurahan Simpang Baru Kecamatan Tampan Kota Pekanbaru) - Lisa Lestari; Titi Maemunaty; Sumardi Sumardi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study examines the parenting style of children's learning activities at home (a study of deaf children in Panam Mulia SLB, Simpang Baru Village, Tampan District, Pekanbaru City). This research uses a descriptive qualitative approach. The informants in this study were 5 (five) people. Data collection is done by means of observation (observation), documentation, interviews. Data analysis is carried out by means of data reduction (data reducation), data display (data display), as well as drawing conclusions and data verification (conclusion drawing / verifying). The results showed that basically the parenting style of children learning activities at home for deaf children is a way for parents to show their attitudes / actions towards their children which aim to look after, care for, guide, teach, educate and train all children's activities related to physical and mental children. And the role of parents who are responsible for the first education for their children. The parenting style applied by parents who have deaf children, namely the first is parenting for parents (NL) using democratic parenting and consultants, the second is parenting for parents (JL) using democratic parenting and merging, the third is parenting. in people (LJ) using authoritarian and militaristic parenting. The fourth is parenting (JM) using pioneer parenting and consultants. Of the four parenting patterns that are best applied to deaf children, namely democratic parenting and consultants because this parenting style, parents always prioritize common interests over individual children's interests and provide themselves as a place for children's complaints, opening themselves up to be good listeners for child. Parents are ready with children to listen to stories, information, news, and complaints about various things that children have brought from their life experiences.Key Words: Parenting, Parent, Learning Activities, Deaf Child